Legal Analysis Of Corporate Social Responsibility In Mining Companies - Su’udi, Su’udi; Borman, M. Syahrul; Handayati, Nur (PT. Anagata Sembagi Education, 2025)
This study analyzes the implementation of the law on Corporate Social Responsibility (CSR) obligations in mining companies in Indonesia. Although CSR has become a legal obligation regulated in Law No. 40 of 2007 concerning Limited Liability Companies and Government Regulation No. 47 of 2012, its implementation still faces various obstacles, including weak supervision and ineffective legal sanctions. The research method used is normative legal research with a legislative and conceptual approach to evaluate the effectiveness of regulations in ensuring companies' compliance with their social responsibilities. The results of the study show that the implementation of CSR in the mining sector tends to be an administrative formality without providing real benefits to the surrounding community. In addition, the incompatibility between national regulations and international standards such as ISO 26000 creates legal loopholes that allow companies to circumvent their CSR obligations. The government needs to strengthen the supervision mechanism, set clearer indicators of CSR success, and implement stricter sanctions for companies that violate legal provisions. Community participation is also an important factor in supervising and evaluating CSR programs in order to provide a more sustainable social and environmental impact..